2015
DOI: 10.3109/09513590.2015.1058355
|View full text |Cite
|
Sign up to set email alerts
|

Relation of metabolic syndrome with endometrial pathologies in patients with abnormal uterine bleeding

Abstract: Metabolic syndrome and its components have been shown to have profound impacts on initiation and progession of endometrial pathology, particularly during post-menopausal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…The same is detected in our study in form of significant increase in serum total cholesterol levels in EH‐induced group compared with control. That is in accordance with Özdemir et al and Romualdi et al . On addition of DIA, it succeeded in normalization of total cholesterol levels compared to EB‐induced EH and atypia due to its anti‐inflammatory, antioxidant, and lipid lowering effects .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The same is detected in our study in form of significant increase in serum total cholesterol levels in EH‐induced group compared with control. That is in accordance with Özdemir et al and Romualdi et al . On addition of DIA, it succeeded in normalization of total cholesterol levels compared to EB‐induced EH and atypia due to its anti‐inflammatory, antioxidant, and lipid lowering effects .…”
Section: Discussionsupporting
confidence: 90%
“…Hypertension, elevated levels of glucose, total cholesterol, LDL‐cholesterol, and reduced levels of HDL‐cholesterol were detected among women with EH and EC . The same is detected in our study in form of significant increase in serum total cholesterol levels in EH‐induced group compared with control.…”
Section: Discussionsupporting
confidence: 88%
“…However, the strength of such an association varies depending on age, BMI, and menopausal status, and one cohort study demonstrated that blood glucose levels are not associated with EC [ 93 ]. Five large-scale case-control studies demonstrated significantly higher blood glucose levels in women with ECs than controls [ 37 , 99 , 100 , 101 , 102 ].…”
Section: Is Diabetes Mellitus No Longer a Risk Factor For Ec?mentioning
confidence: 99%
“…30,31 Abnormalities in endometrium are noted due to diabetes, obesity, hyperglycemia, and hyperlipidemia. 32 F I G U R E 1 Various phenotypes of polycystic ovary syndrome PCOS patients also appear to have increased levels of palmitoyl sphingomyelin (SM), cyclic guanosine monophosphate (cGMP), and dehydroepiandrosterone sulfate (DHEAS). 33 Elevated levels of sphingolipids are also one of the significant findings in CVD.…”
Section: Cardiovascular Diseases Metabolic Syndrome and Diabetes mentioning
confidence: 99%